2016
DOI: 10.1371/journal.pone.0164063
|View full text |Cite
|
Sign up to set email alerts
|

Lowered Expression of Tumor Suppressor Candidate MYO1C Stimulates Cell Proliferation, Suppresses Cell Adhesion and Activates AKT

Abstract: Myosin-1C (MYO1C) is a tumor suppressor candidate located in a region of recurrent losses distal to TP53. Myo1c can tightly and specifically bind to PIP2, the substrate of Phosphoinositide 3-kinase (PI3K), and to Rictor, suggesting a role for MYO1C in the PI3K pathway. This study was designed to examine MYO1C expression status in a panel of well-stratified endometrial carcinomas as well as to assess the biological significance of MYO1C as a tumor suppressor in vitro. We found a significant correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…3h). This is in agreement with a study in human cancer cells, which showed a higher proliferation rate after Myo1C depletion 22 . To understand this in more detail, we studied the cell cycle distribution of propidium iodide-stained WT and KO cMEFs by flow cytometry (Fig.…”
Section: Resultssupporting
confidence: 93%
“…3h). This is in agreement with a study in human cancer cells, which showed a higher proliferation rate after Myo1C depletion 22 . To understand this in more detail, we studied the cell cycle distribution of propidium iodide-stained WT and KO cMEFs by flow cytometry (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The result is consistent with the involvement of myosin IC in the free locomotion of retinal and mammary epithelial cells 14 , 15 . In the normal mammary cells, the reduction of free locomotion was connected with a reduction of cell adhesion and spreading, and linked to a loss of contact inhibition 15 . It is likely that the migration of the transformed prostate epithelial cells involves the same mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…Myosin IC is involved in the motility of the neuronal growth cones 13 , and recent work established a role for myosin IC in the motility of retinal and mammary epithelial cells in vitro 14 , 15 . The methods employed in these studies did not distinguish between the isoforms, and the cell types were not among the few identified as expressing isoform A 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Myosin-1C ( MYO1C ), another important gene in the PI3K / AKT signalling pathway, is known to bind with PIP2 and potentially acts as a tumour suppressor [ 52 , 53 ]. MYO1C has also a role in glucose uptake and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%